Wastewater treatment and biogas recovery using anaerobic membrane bioreactors (AnMBRs): strategies and achievements - Musa, Mohammed Ali; Idrus, Syazwani; Che Man, Hasfalina; Nik Daud, Nik Norsyahariati (MDPI, 2018)
Anaerobic digestion is one of the most essential treatment technologies applied to industrial and municipal wastewater treatment. Membrane-coupled anaerobic bioreactors have been used as one alternative to the conventional anaerobic digestion process. They are presumed to offer the advantage of completely reducing or minimizing the volume of sludge and increasing biogas production. However, researchers have consistently reported different kinds of fouling that resulted in the reduction of membrane life span. Depending on the strength of the effluent, factors such as high suspended and dissolved solids, fats, oil and grease, transmembrane pressure (TMP) and flux were reported as major contributors to the membrane fouling. Moreover, extracellular polymeric substances (EPSs) are an important biological substance that defines the properties of sludge flocs, including adhesion, hydrophobicity and settling and have been found to accelerate membrane fouling as well. Extensive studies of AnMBR have been done at laboratory while little is reported at the pilot scale. The significance of factors such as organic loading rates (OLRs), hydraulic retention time (HRT), pH and temperature on the operations of AnMBRs have been discussed. Microbial environmental conditions also played the most important role in the production of biogas and the chemical oxygen demand (COD) removal, but adverse effects of volatile fatty acids formation were reported as the main inhibitory effect. Generally, evaluating the potential parameters and most cost effective technology involved in the production of biogas and its inhibitory effects as well as the effluent quality after treatment is technically challenging, thus future research perspectives relating to food to microorganism F/M ratio interaction, sufficient biofilm within the reactor for microbial attachment was recommended. For the purpose of energy savings and meeting water quality discharge limit, the use of micro filtration was also proposed.